DIVERSITY OF MAKROZOOBENTHOS IN THE FISH-SHRIMP POND AREAS IN ULEE MATENG VILLAGE - Pradana, Gilang; Putra, Chairunas Adha; Mustaqim, Mustaqim; Mukra, Rizal; Hafzari, Rini (Universitas Negeri Medan, 2024)
Makrozoobenthos plays a crucial role in ecosystems as producers, primary consumers, and decomposers or detritus that can degrade organic compounds into inorganic ones. As primary consumers, the role of makrozoobenthos is vital for the survival of wildlife, especially various species of shorebirds commonly found in coastal areas and fish-shrimp pond areas. The aims of this research is determining the abundance of makrozoobenthos (ind/m3) and ecological index at the pond in Ulee Matang Village. The diversity of macrozoobenthos species in the area consists of 12 species of three phylum and six classes. The abundance of macrozoobenthos on two type of pond (fish and shrimp) are ranging from 892 ind/m3 to 1400 ind/m3. The Arthropoda phylum, abundant in the research area, notably featured the Water Flea Daphnia sp. that serving as a primary food source for fish and shrimp prior to the introduction of fish and shrimp seeds. This suggests a significant role of arthropods in the food chain, supporting not only fish and shrimp but also macrozoobenthos and shorebirds.